Pest categorisation of Beet curly top virus (non‐EU isolates). (11th October 2017) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Gregoire, Jean‐Claude; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; Niere, Björn; Parnell, Stephen; et al.
Abstract: The EFSA Panel on Plant Health performed a pest categorisation of non‐EU isolates of Beet curly top virus (BCTV) for the European Union territory. The virus causes severe diseases in beet, tomatoes and pepper crops, occurs predominantly in warm and dry zones and is reported from many countries outside the EU in particular from western USA and Mexico. New data from complete virus genomes make BCTV a well characterised virus species of which currently 11 strains are known and for which diagnostic methods are available. BCTV has a very broad host range of more than 300 species some of which may remain symptomless. Aside from vegetative propagation of infected plants, the only mode of BCTV transmission and spread is by the leafhopper Circulifer tenellus which efficiently transmits the virus in a persistent mode and which is present in several southern EU Member States. No current reports of BCTV presence in the EU exist and because of doubts about the accuracy of older reports, BCTV likely is absent from the EU territory. BCTV can enter into the EU with viruliferous insects and with imports of plants not subject to specific EU regulation. Because both the virus and its vector have a wide host range, BCTV is expected to establish and spread in the Member States where its vector is present and to cause severe diseases in sugar beet and tomato as well as in other crops. Overall, BCTV non‐EU isolates meet all the criteria evaluated by EFSA to qualify as a Union quarantine pest and do not meet the criterion of presence in the EU to qualify as a Union regulated non‐quarantine pest (RNQP). The main uncertainties concern (1) the presence of BCTV in the EU, (2) the distribution of C. tenellus and (3) the main commodities for virus entry.